Block-diagonal reduction of matrices over an $n$-simple Bézout domain $(n ≥ 3)$ - Domsha, O.V.; Zabavskii, B. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
It is known that a simple Bézout domain is the domain of elementary divisors if and only if it is 2-simple. The block-diagonal reduction of matrices over an $n$ -simple Bézout domain $(n ≥ 3)$ is realized.